Modeling service systems - Badinelli, Ralph D. (Service systems and innovations in business and society collection., 2016)
This book invites the reader on a journey of discovery of service systems. From a Service-Dominant-Logic perspective, such systems are the building blocks of all economic activity, and innovation of new service systems holds the promise of a new industrial revolution. Users navigating websites, customers interacting with intelligent mobile retail applications, patients interpreting advice from health-care professionals and other sources, students interacting with teachers and learning materials, city dwellers invoking smart service applications for transportation routing, and the unlimited variations of smart service systems that will be enabled by the Internet of Things and other technologies provide ample evidence of the need for service innovation. Fundamentally human centered and cocreative, these services must engage actors in personalized journeys directed by their decisions. Hence, understanding the performance of service systems and designing better service systems require an understanding of how actors or their agents make decisions and how service systems should enable and respond to these decisions. Service science is the study of such systems and decisions. This book presents an overview of the foundational constructs of service science and models of cocreative systems, with the aim of enabling the reader to be a service innovator. Consequently, the book's title expresses the purpose of the book in terms of initiating the reader in the action of modeling as opposed serving as a presentation of models for observation. Some readers may possess in-depth knowledge of some aspects of service systems that this text only surveys. That's fine. The value proposition of this book is the opportunity to fill each reader's knowledge gaps and offer a comprehensive, coherent, and introductory overview of service system modeling.